2014
DOI: 10.1080/00140139.2014.985260
|View full text |Cite
|
Sign up to set email alerts
|

Workplace slip, trip and fall injuries and obesity

Abstract: The objective of this study was to examine the relationship between slip, trip and fall injuries and obesity in a population of workers at the Idaho National Laboratory (INL) in Idaho Falls, Idaho. INL is an applied engineering facility dedicated to supporting the US Department of Energy's mission. An analysis was performed on injuries reported to the INL Medical Clinic to determine whether obesity was related to an increase in slip, trip and fall injuries. Records were analysed that spanned a 6-year period (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
1
21
1
Order By: Relevance
“…17,39 Although other previous studies did not show a significant relationship between underweight status and falls, these studies were confined to the elderly or only included a small portion of the study population classified as underweight. 11,40 …”
Section: Discussionmentioning
confidence: 99%
“…17,39 Although other previous studies did not show a significant relationship between underweight status and falls, these studies were confined to the elderly or only included a small portion of the study population classified as underweight. 11,40 …”
Section: Discussionmentioning
confidence: 99%
“…This may cause physical incapability to perform work and daily activities. For instance, obese individuals may be more prone to balance loss and falling than non-obese individuals during a prolonged standing task (Koepp et al, 2014 Dec 22;Mehta and Cavuoto, 2015;Peduzzi de Castro et al, 2014 Jul). Although Strigel et al did not consider specific work demands in relation to overweight and obesity, the authors reported the association between obesity and work impairment and they assessed WF by the Work Productivity Activity Impairment questionnaire (Striegel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Being overweight was found to be related to falls on the same level among male construction workers (Chau et al 2004). Similarly, Koepp, Snedden, and Levine (2015) found obesity to be related to slip, trip and fall injuries among workers at an applied engineering facility. A recent gait experiment involving young obese adults suggests that slip-induced fall risks are higher along the transversal direction due to wider step width (Wu, Lockhart, and Yeoh 2012).…”
Section: Epidemiologymentioning
confidence: 91%